The Dialectic of Decadence and the Abyss of Freedom: An Ontological Interpretation of Augustine's Origin of Evil - LV, Chao (Journal of Research for Christianity in China (JRCC), 2025)
Augustine regarded the first evil will preceding all external sins—namely, “pride” (superbia), the will or love of the heart turning away from God toward itself—as the original fall of humanity's ancestors, thereby establishing the classic Christian theological explanation for the origin of evil. However, in recent decades, Anglo-American scholars have sharply questioned the validity of this interpretation of Augustine: for in Augustine's account, the first human ancestors fell suddenly while possessing full wisdom, a good nature, and being free from pressure or temptation. In contrast, scholars represented by Babcock argue that the abrupt mutation of the will from good to evil— —this “discontinuity” between the volitional act and the agent's prior state makes the act not only difficult to attribute to the agent but also seemingly incomprehensible to reason.Faced with the difficulties encountered by Anglo-American scholars in psychological discussions, this paper takes a different approach. Moving beyond the psychological level to the ontological level, it draws upon Augustine's Neoplatonic ontology. By examining the positions and relationships of humans and God within the “hierarchy of being,” and by analyzing the “dialectical unity” of two opposing actions within the same evil will—namely, “falling into nothingness” and “seeking God”— and by revealing the potential misalignment between the “order of love” and the “order of goodness.” This approach will demonstrate the “eternal motive for fallenness” rooted in the “legislative capacity” of free will. Consequently, fallenness can not only be readily attributed to the free being itself but also become, to a certain extent, rationally comprehensible. This paper will demonstrate that this motive for fall transcends all psychological phenomena and is embedded within the very structure of freedom. Viewed positively, it functions as an inherent defect in the freedom of finite beings themselves—like a dark abyss within freedom itself— eternally accompanying and tempting him toward fall. Conversely, as proof of the finite being's innate legislative capacity as the “image of God,” it manifests his sacred potential to transcend toward God in love and unite with God in love.